A sudden presentation of abdominal compartment syndrome - Berkman, Tolga; Naftalovich, Rotem; Oydanich, Marko; Iskander, Andrew J.; Naftalovich, Daniel (Anestezjologia Intensywna Terapia, 2021)
Abdominal compartment syndrome (ACS) is defined as sustained intra-abdominal pressure (IAP) exceeding 20 mm Hg, which causes end-organ damage due to impaired tissue perfusion, as with other compartment syndromes [1, 2]. This dysfunction can extend beyond the abdomen to other organs like the heart and lungs. ACS is most commonly caused by trauma or surgery to the abdomen. It is characterised by interstitial oedema, which can be exacerbated by large fluid shifts during massive transfusion of blood products and other fluid resuscitation [3]. Normally, IAP is nearly equal to or slightly above ambient pressure. Intra-abdominal hypertension is typically defined as abdominal pressure greater than or equal to 12 mm Hg [4]. Initially, the abdomen is able to distend to accommodate the increase in pressure caused by oedema; however, IAP becomes highly sensitive to any additional volume once maximum distension is reached. This is a function of abdominal compliance, which plays a key role in the development and progression of intra-abdominal hypertension [5]. Surgical decompression is required in severe cases of organ dysfunction – usually when IAPs are refractory to other treatment options [6]. Excessive abdominal pressure leads to systemic pathophysiological consequences that may warrant admission to a critical care unit. These include hypoventilation secondary to restriction of the deflection of the diaphragm, which results in reduced chest wall compliance. This is accompanied by hypoxaemia, which is exacerbated by a decrease in venous return. Combined, these consequences lead to decreased cardiac output, a V/Q mismatch, and compromised perfusion to intra-abdominal organs, most notably the kidneys [7]. Kidney damage can be prerenal due to renal vein or artery compression, or intrarenal due to glomerular compression [8] – both share decreased urine output as a manifestation. Elevated bladder pressure is also seen from compression due to increased abdominal pressure, and its measurement, via a Foley catheter, is a diagnostic hallmark. Sustained intra-bladder pressures beyond 20 mm Hg with organ dysfunction are indicative of ACS requiring intervention [2, 8]. ACS is an important aetiology to consider in the differential diagnosis for signs of organ dysfunction – especially in the perioperative setting – as highlighted in the case below.